Seventy Years of the International Law Commission Drawing a Balance for the Future (Brill, 2020)
Seventy Years of the International Law Commission: Drawing a Balance for the Future brings together voices from academia and practice to celebrate and critically evaluate the work of the United Nations International Law Commission (ILC) over the past seventy years. The edited volume draws on the events commemorating the seventieth anniversary of the Commission, which took place in New York and Geneva in May and July 2018. At a time when multilateral law-making has become increasingly challenging, the edited volume appraises the role of one the most important driving forces behind the codification of international law and discusses the ILC's future contribution to the development of international law. Readership: The prospective readership of the edited volume will be very diverse, including academics and practitioners of international law around the world.